On physical analysis of synthesis strategies and entropy measures of dendrimers - Muhammad Imran (Elsevier, 2022)
Dendrimers achieved great consideration in gene and drug delivery applications because of having highly administrable architecture. Unambiguous structure of dendrimers might reduce the unpredictability related to the molecule’s shape and size, and also boost the accuracy of drug delivery. Dendrimers have exclusive physical and chemical properties due to which they have extensive range of potential applications like chemical sensors, light harvesting material, enhance the solubility, antitumer therapy, medical diagnostics, drug delivery system, catalysts, and many more. With the total π-electron energy, the degree-based topological indices have a lot of iterations.In this paper, our desideration is to compute the topological aspects of degree based entropy for fractal and cayley tree type dendrimers. More preciously, we explore two tree type dendrimers denoted by Fr ant Cm,n. Moreover, entropies are estimated of these two structures by generating a correlation between degree based topological indices and their entropies.